Cytotoxic T‐lymphocyte‐associated protein 4 expressed by melanoma cells does not affect melanoma‐specific cytotoxic T lymphocytes in the effector phase. Issue 1 (27th October 2018) - Inozume, Takashi; Hanada, Ken‐ichi; Takeda, Kazuyo; Maeda, Tatsuo; Harada, Kazutoshi; Kawamura, Tatsuyoshi
Abstract: Cytotoxic T‐lymphocyte‐associated protein 4 (CTLA‐4) is one of the important molecules that regulate the anti‐melanoma T‐cell response. Currently, there are some reports showing that CTLA‐4 is expressed not only by T cells but also by various kinds of tumor cells, including melanoma cells. However, there is no report that shows the role of CTLA‐4 expressed by melanoma cells in melanoma‐specific cytotoxic T‐lymphocyte (CTL) response. In this report, we confirmed substantial CTLA‐4 expression and the localization of CTLA‐4 in melanoma cell lines and tissues. Also, we examined its impact on melanoma‐specific CTL in vitro, and found that CTLA‐4 expressed by melanoma cells does not affect melanoma‐specific CTL in the effector phase. Our findings suggest the importance of elucidating the role of CTLA‐4 expressed by melanoma cells, particularly in anti‐CTLA‐4 antibody therapy.